Pengaruh insentif terhadap kinerja karyawan pada sicepat ekspres Cabang Majalengka - Said, Ade Bagus; Maman Kusman (Program Studi Akuntansi IKOPIN, 2022)
has a significant effect on employee performance at Sicepat Ekspres Majalengka Branch. The purpose of this study was to determine whether there is an effect of providing incentives on employee performance.The type of research used is quantitative with an associative approach. Data collection techniques through observation, questionnaires, and documentation. While the data analysis technique used is simple linear regression. Correlation coefficient analysis, determination coefficient analysis, and t-test. As for the types of data sources, this research is primary data, namely data obtained directly from the original or place where the research is carried out. The population of this research is all employees of Sicepat Ekspres Majalengka Branch, totaling 25 people. Determination of the sample is saturated sampling. The results of this study indicate that based on the results of research conducted by researchers at Sicepat Ekspres Majalengka Branch that the provision of incentives has a significant effect on employee performance. This can be seen from the results of statistical calculations through partial hypothesis testing, which shows that t count > t table then Ha is accepted and Ho is rejected.